Kajian Kesejahteraan Rakyat dan Kesejahteraan Negara di Indonesia - Tukino Tukino (Bina Nusantara University, 2012)
The goal of the article was to remind the state authorities in order to realize that Indonesia was set up aiming for the welfare of the people. Qualitative research was conducted. Data obtained from literature studies and field observations. The analytical method used was descriptive analysis. The results indicate that Indonesia are often far from people's expectations. Authorities, especially of late just thinking about state power without thinking about the lives of the people in general. Indeed, attention to the people of Indonesia by a regime that ever existed up and down sometimes. However, in recent times with the number of cases that exist in the country of Indonesia plus the slogan 'the autopilot' illustrates that the country further and further away from the people themselves. Therefore, the need for Indonesia to return the State Government to be more focused on the welfare of the people widely in the framework towards the welfare state because that is true the goals of Indonesia country was built.